PHYSICAL EDUCATION TRAINING CHALLENGES TO MEET INCLUSION IN PARAÍBA (Fiep Bulletin - online, 2025)
Objectve: To analyze the knowledge/training and difficulties of Physical Education teachers in the state of Paraíba regarding the inclusion of people with disabilities. Methods: The sample consisted of 380 participants, Physical Education teachers from the state of Paraíba, from all school systems (men, n = 281 and women, n = 99). A semi-structured questionnaire, composed of closed questions, was used as the instrument for data collection. Results: Most teachers are assigned to state schools (69.47%) and are male (73.95%), and 67.1% have knowledge about Special Physical Education and/or Adapted Physical Education. However, the academic training of Physical Education teachers does not contemplate the need for the professional to work with people with disabilities. This generates insecurity when defining whether students are eligible and 196 teachers indicate that they are unable to include a student with a disability in their classes. And they justify this due to the lack of physical structure and material, as well as lack of knowledge in the area/prepared professional. Conclusion: Teachers have knowledge about Special Physical Education and/or Adapted Physical Education, however, the academic training of the Physical Education teacher does not contemplate the need for the professional to work with people with disabilities, which generates insecurity when including a student with a disability in their classes.
Keywords: Physical Education; Inclusion; Training; Person with disabilities